IMPROVING STUDENT LEARNING AND ACTIVITIES PARTICIPATION WITH COOPERATIVE JIGSAW LEARNING METHODS ON LEARNING PRODUCTION PROCESS AND MACHINERY CONSTRUCTION IN VOCATIONAL SCHOOL - Abdurrahman Abdurrahman; Deddy Supriyatna (Universitas Sultan Ageng Tirtayasa, 2019)
This research is a classroom action research that aims to provide solutions on how to solve learning difficulties faced by class XI students of Industrial Mechanical Engineering, SMK Negeri 4 Cilegon, which are related to the subject of machine production and construction processes. At this time the learning method uses the Student Teams-Achievement Divisions (STAD) model which is packaged modularly, in the hope that students can develop their own potential independently so that they can complete the learning material thoroughly (mastery learning) but student achievement still does not show the expected results. The implementation of this class action research was conducted in two cycles using JIGSAW cooperative learning methods that can improve student achievement and student activity participation. This result can be seen from the first formative test, where the class average value is 4.05, and through observing the percentage of student activity participation of 50.92%. After classroom action research (CAR) was held the student learning outcomes showed a significant increase. In the first cycle, the formative test results obtained a mean grade value of 5.54 and student activity participation of 52.38% (very good). In the second cycle, the formative test results obtained a mean grade value of 6.20 and student activity participation of 66.67% (very good). As for the learning completeness criteria, the first cycle was obtained 52.38%, the second cycle was 66.67%.